Helicobacter pylori infection: a dynamic process from diagnosis to treatment - Sun, Qifang; Yuan, Chengzhi; Zhou, Sainan; Lu, Jing; Zeng, Meiyan; Cai, Xiong; Song, Houpan (Frontiers in Cellular and Infection Microbiology, 2023)
Helicobacter pylori, a gram-negative microaerophilic pathogen, causes several upper gastrointestinal diseases, such as chronic gastritis, peptic ulcer disease, and gastric cancer. For the diseases listed above, H. pylori has different pathogenic mechanisms, including colonization and virulence factor expression. It is essential to make accurate diagnoses and provide patients with effective treatment to achieve positive clinical outcomes. Detection of H. pylori can be accomplished invasively and noninvasively, with both having advantages and limitations. To enhance therapeutic outcomes, novel therapeutic regimens, as well as adjunctive therapies with probiotics and traditional Chinese medicine, have been attempted along with traditional empiric treatments, such as triple and bismuth quadruple therapies. An H. pylori infection, however, is difficult to eradicate during treatment owing to bacterial resistance, and there is no commonly available preventive vaccine. The purpose of this review is to provide an overview of our understanding of H. pylori infections and to highlight current treatment and diagnostic options.